Penguatan Branding dan Pemasaran Digital UMKM Kerupuk Kulit Desa Tanjung Rancing Tahun 2026 - Muslimin Muslimin; Army Juwita Permadani; Adin Adin; Adiska Salsabial; Amelia Puspita Nadi; Ahmad Hazarul Aswadi; Allya Della Syahfitri; Ainaya Dinda; Andriani Nurohmah; Abel Alamsyah; Adellia Patricia Putri; Alfrida Widyandari; Siska Lidia; Juliana Yud; Andi Hasnawati (JURNAL PENGABDIAN KADER BANGSA, 2026)
This community service activity aims to improve branding and digital marketing capabilities for the kerupuk kulit SME owned by Mr. Boni in Tanjung Rancing Village. The main problems faced by the partner include limited knowledge of modern marketing strategies, lack of strong brand identity, and minimal use of digital media for product marketing. The methods used in this program include field observation, interviews with SME actors, branding training, and digital marketing assistance through social media and marketplace platforms. The activities also include designing product logos, improving packaging, and creating social media accounts as promotional media. The results indicate an increase in the partner's understanding of branding and digital marketing strategies, as well as wider marketing reach for the kerupuk kulit product. With improved branding strategies and the use of digital media, it is expected that the kerupuk kulit product owned by Mr. Boni will become more widely recognized and increase its sales performance. This program demonstrates that strengthening branding and digital marketing can be an effective solution to enhance the competitiveness of SMEs in the digital era.